Cardless E-ATM With Secured Biometric Authentication Using Labview - K.S.Dhanalakshmi, A.Sindhu, S. Selvakumar, S. Subabalasathiya, R.Karthick (International Journal of Advanced Science and Technology, 2020)
This work presents about the electronic banking outlet that allows bank customers to complete one or more banking transactions. The customer is identified by biometric to control access to the ATM for money withdrawals, balance enquiry, deposit. The user of existing ATM machine uses card with the magnetic strip bar code to access their financial transactions. Several problems arose with the use of  cards such as card cloning, fake card, card damaging, card expiring ,cost skimming, cost of issuance and maintenance, accessing customer transactions by third parties, waiting time before issuance expiring or new card.  The entire problem associated with the use of ATM can be eliminated if we have the use of cardless ATM. The objective of the project is to design a cardless ATM that uses biometric access control system. Biometrics can be defined as a measurable physiological and behavioral characteristic that can be subsequently compared & captured with another instance at the time of verification. These technologies are a secure way of authentication because data of both technologies are unique, cannot be shared, cannot be copied and cannot be overlooked.